Uncommon Property: The Fishing and Fish-Processing Industries in British Columbia; Salmon: The Decline of the British Columbia Fishery - Neis, Barbara (Labour / Le Travail, 1992)
The article reviews two books: "Uncommon Property: The Fishing and Fish-Processing Industries in British Columbia," edited by Patricia Marchak, Neil Guppy, and John McMulla, and "Salmon: The Decline of the British Columbia Fishery," by Geoff Meggs.
Keywords: BOOKS -- Reviews; GUPPY, Neil; MARCHAK, Patricia; MCMULLA, John; MEGGS, Geoff; Nonfiction; SALMON: The Decline of the British Columbia Fishery (Book); UNCOMMON Property: The Fishing & Fish-Processing Industries in British Columbia (Book)